(untitled) (Bangladesh Journal of Medical Science, 2023)
Aim: To assess and compare the efficiency of tooth movement in patients subjected to piezocision and photobiomodulation as part of a split-mouth clinical experiment, and to combine their effects in order to derive a synergetic effect if any. Methods: 24 subjects requiring bilateral first premolar extractions were selected for the study. The study had a split mouth design with patients subjected to either piezocision, photobiomodulation or a combination of the two techniques in one quadrant and the opposite quadrant served as the control. Piezocision was carried out by placing vertical interproximal incisions on the mesiobuccal and distobuccal aspect of the maxillary canine, whereas photobiomodulation was carried out at ten sites, five on the buccal aspect and five on the palatal aspect with a total energy of 10J in the period between the three weeks. Results: There was no statistically significant difference observed in terms of accelerated tooth movement between piezocision, photobiomodulation or combination of the two techniques and the conventional technique. Conclusion: Although no statistically significant findings were derived, a synergistic effect was observed with the combined effect of piezocision and photobiomodulation showing an enhanced effect. Increased rate of tooth movements were observed in both piezocision and photobiomodulation group with lowest effect seen in the photobiomodulation group. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.138-147